The Values of Local Wisdom of the Ngumbai Lawok Tradition as a Source of History Learning - Khoiriyah, Febriana; Miftahuddin; Sumargono; Fahri, Ardian (Universitas Islam Negeri Raden Intan Lampung, 2025)
The coastal communities of Lampung have a tradition known as Ngumbai Lawok, which is closely tied to their livelihood as fishermen. This study aims to explore the local wisdom embedded in the Ngumbai Lawok tradition in the Lampung Coastal Regency and assess its potential as a source for teaching local history and culture. A qualitative approach, using ethnographic methods, was employed for data collection through observation, interviews, and literature review. The findings reveal that the Ngumbai Lawok tradition encompasses cultural values, including religious, social, cultural, and educational aspects. These cultural values can be integrated into history instruction, particularly for high school students in grade X, stage E. The inclusion of the Ngumbai Lawok tradition as an alternative source for local history education is essential for enhancing historical awareness and fostering a stronger sense of local identity and character among the people of Lampung. Furthermore, this study highlights the relevance of local traditions in modern education and their ability to bridge the gap between cultural heritage and contemporary learning approaches. The integration of such traditions into the curriculum can also promote a deeper understanding of the role of culture in shaping regional identity.